Investigate and Prepare silver Nano Particles Using Jet Plasma - Noori, Aiyah S.; Aadim, Kadhim A.; Hussein, Alyaa H. (Iraqi Journal of Science, 2022)
Nano- particles (Ag NPs) are synthesized by using plasma Jet argon gas. The prepared Ag NPs are characterized by Atomic Absorption Spectroscopy (AAS) The measure was performed for different time exposuring 15,30,45 and 60 sec. The results shows the low concentration of nano-silver time expose (15 sec) and very) and high concentration at 60 sec. The UV-VIS spectrometer for nano-silver different time exsposuring to plasma, shows the Surface Plasmon Resonance (SPR) appeared around 419 nm, and the energy gab is 4.1 eV for the 15 second exposure and 1.6eV for 60 second exposure. The Scanning Probe Microscope (SPM) is used to identify the characterization of silver nanoparticles, the average diameter of nano-silver for 15 second exposure is equal to 69.00 nm, for 60 second exposure the average is equal to 54.87 nm